Assessment of knowledge and practices of hygienic milk production among dairy farmworkers, Southwest Delhi - Ikra Ahmed; Sumesh Kumar; Divya Aggarwal (Wolters Kluwer Medknow Publications, 2020)
Introduction: India has emerged as the highest milk-producing country in the world, with an annual production of 137.7 million tones (2013-2014). The quality of contaminated milk deteriorates quickly and produces diseases if consumed. Therefore, care has to be taken in production, storage, and transport of milk. Knowledge about hygienic milk production practices is essential for proper health and nutrition. However, an assessment of their knowledge of hygienic milk production practices has not been carried out in a systematic manner. Objective: This study aims at assessing the knowledge and practices of hygienic milk production among small dairy farmers in the peri-urban area of Southwest Delhi. Methodology: This exploratory cross-sectional study is conducted among 60 dairy farmworkers, selected conveniently from Southwest Delhi. Practices and knowledge levels are assessed using a pretested semi-structured questionnaire. Results: The desired outcome indicates the knowledge level of dairy farmworkers regarding clean milk production practices. Conclusion: Knowledge level -It can be observed that 66.6% of the dairy farmworkers belong to category 2 (medium), whereas 13.3% and 20% of dairy farmworkers belong to category 1 (low) and 3 (high), respectively. Practice level -This study indicates that 60% of the dairy farmworkers belong to category 2 (medium), followed by 21.6% and 18.3% of the dairy farmworkers belong to category 1 (low) and 3 (high), respectively.